Cryptography: A Combination of Caesar and Affine Cipher to Conceal the Message - Wulandari, Septi Yana (Proceeding International Conference on Science and Engineering, 2020)
Advances in technology make it easy for humans to communicate with each other. One of them is by sending messages. However, the confidentiality of messages can be hacked by third parties. Therefore, it is necessary to secure the messages sent so that confidentiality can be maintained. One way that can be done to maintain message security is cryptography. Classical cryptography has several types of algorithms including caesar cipher and affine cipher. The purpose of this study is to combine caesar cipher and affine cipher as one technique that can be used to secure messages. This combination is done by changing the plaintext into ciphertext 1 through caesar encryption. Ciphertext 1 is encrypted by affine caesar to produce ciphertext 2. Ciphertext 2 is the message to be sent. Then to change to original message ciphertext 2 is decrypted by affine chiper so that it gets plaintext 1. Then plaintext 1 is decrypted by caesar chiper so that it gets plaintext 2. Plaintext 2 is the message that should be received. The result of this study are a combination of caesar cipher and affine cipher can secure a message sent.